Pengaruh Worklife Balance Dan Lingkungan Kerja Terhadap Kinerja Karyawan: Studi Pekerja Tambang PT.Citra Silika Mallawa Kel. Lasususa, Kab. Kolaka Utara - Mardiana Mardiana; H. Suwarto; Fitri Kumalasari (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
This study aims to determine: (1) The effect of work life balance on employee performance PT. Citra Silika Mallawa Kel. Lasusua Kab. Kolaka Utara. (2) The Effect of the Work Environment on Employee Performance at PT. Citra Silika Mallawa Kel. Lasusua Kab. Kolaka Utara. This research uses a quantitative method approach. Collecting data in this study using interviews, literature study, and distributing questionnaires. The population of this study were all employees of PT. Citra Silika Mallawa Kel. Lasusua Kab. Kolaka Utara. The sample for this study was 184 people. Testing research instruments using validity and reliability tests with SPSS 25.0. The data analysis technique used in this study is the measurement model test (outer model) and the structural model test (inner model) with Smart PLS 4.0. Based on the results of the study it is known that there is a positive and significant influence between the work life balance variables as shown by the P-Value of 0.021. While the work environment variable has a positive and significant effect on nurse performance as shown by the P-Value of 0.000.